Queering Engineers? Using History to Re-think the Associations Between Masculinity and Irrigation Engineering in Peru. Issue 2 (4th May 2017) - Vera Delgado, Juana R.; Zwarteveen, Margreet
ABSTRACT: The analysis in this article contrasts indigenous irrigation systems with modern water engineering in Peru to denaturalize and de-normalize the binary gendered associations through which the modern engineering water profession has come to be defined. We present evidence that suggests a gradual historical change in the main source(s) and bearers of water authority in Peru; from the divine to science and from priests to modern engineers. This change has gone accompanied with a distinct masculinization of formal water rights and powers. Yet, remnants from the earlier and more gender-dual past remain visible in actual water distribution and governance processes, which mix and combine more modern engineering knowledges with insights from Inka and pre-Inka histories. By not a priori singling out men as the privileged bearers of water expertise or authority, these hybrid forms of water management in Peru may provide promising entry-point for designing and constructing systems that are better attuned to the combined goals of environmental sustainability and social equity, while also helping make the water engineering profession more hospitable to women and 'non-modern' men.